Malmesbury Abbey
The south doorway of Malmesbury Abbey was built in William of Malmesbury's day, but the foundation of the Benedictine church dates from King Ina. Adhelm, the founder of the Saxon church of Bradford on Avon, was educated in the community here, and he became the first abbot. The open stonework over the porch, and the pointed clerestory windows are of later date.